Confusion and Hallucination: A Case Report of an Unusual Presentation of COVID-19 - Aljumaiah, Rawabi; Alturaiki, Wael; Alosaimi, Bandar (Case Reports in Psychiatry, 2021)
Besides respiratory symptoms, COVID-19 disease has a wide range of clinical, subclinical, and atypical presentations reported previously. Here, we report the case report of a middle-aged man, with no previous known medical illness, who presented with a 5-day-history of anxiety, fever, confusion, and hallucinations. Patient’s SARS-CoV-2 polymerase chain reaction test was positive, and he underwent daily vital signs and respiratory, cardiovascular, and abdominal examinations. Chest radiography, electrocardiogram, microbial culture, biochemistry, and toxicology tests were also investigated. In this report, a case of COVID-19 is described with an unusual presentation of confusion and hallucinations in the absence of severe upper respiratory or constitutional symptoms. The earlier recognition of atypical manifestation, the safer the practice, with optimal timely diagnosis, and less anticipated outbreaks in healthcare facilities. Further studies are needed to establish the underlying pathophysiological mechanisms involved.